Learning and not learning from experience in rural project planning - Hulme, David (Public Administration and Development, 1989)
The theme of learning from experience as a means of improving the effe ctiveness of rural development projects and programmers has been commo n in recent years. Considerable effort has been put into refining, mon itoring and evaluation systems to enhance organizational learning proc esses. However, an emphasis on normative approaches to evaluation and learning from experience has led to the neglect of research into the a ctual processes by which rural development agencies utilize experience . The case study presented here points to the shortcomings of such app roaches and illustrates the partisan manner in which individuals and o rganizations treat the lessons of experience. Actively ‘not learning f rom experience’ is as much a part of organizational processes as learn ing from experience. This paper examines the implications of this find ing and reviews alternative approaches to improving experiential learn ing in rural development activities. It is found that such a perspecti ve does not generate the innocuous technical prescriptions characteris tic of conventional approaches, but a number of useful directions for further research can be identified.